Methodical Foundations of Organizational and Economic Concept Formation of Energy Saving (Economics and region, 2021)
The main principle of Ukraine's economy is to build an energy-efficient society, implement energy-saving programs and projects. The main approaches by domestic and foreign scientists to the interpretation of the organizational and economic mechanism of energy saving are studied. The main tasks of the concept are defined. The principles of economy, responsibility, integrity, complexity are formed, which is the basis of the developed methodology. The criteria for evaluating the effectiveness of the organizational and economic concept of energy saving are summarized. The method of forming the concept of energy saving is proposed and the essence of each stage is revealed. Sources of financing for the implementation of energy saving projects have been identified. Motivational measures and methods of stimulating the introduction of energy saving measures are revealed. The obtained effects from the implementation of the concept of energy saving are indicated.
Keywords: energy saving; mechanism; principles; criteria; motivation; stimuli